STUDI PENGARUH FAKTOR-FAKTOR PENGGUNAAN BRIMO DI SAMARINDA - Feti Fahmimroah; Sri Wahyu Lidya Nur; Siti Nurhasanah; Renita Kawuryan, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
This study examines how ease of use, service quality, trust, and security affect the decision to use the BRImo mobile banking application in Samarinda. Using a quantitative approach, data were collected through online questionnaires distributed using purposive sampling. The responses were analyzed with SPSS version 26, employing various statistical techniques including validity and reliability tests, classical assumption tests, multiple linear regression, hypothesis testing (both partial and simultaneous), and a determination coefficient test. The findings revealed that both ease of use and service quality significantly influence users' decisions to use BRImo. However, trust and security were found to have no significant individual impact. Nonetheless, when considered together, all four variables - ease of use, service quality, trust, and security - collectively have a significant influence on users’ decisions to use the BRImo application.